The effect of moisture conditions on the constitution of two bioceramic-based root canal sealers - Al-Haddad, A.Y.; Kutty, M.G.; Abu Kasim, N.H.; Che Ab Aziz, Zeti Adura (2017)
Background/purpose Intraradicular moisture is not standardized and alters the sealing properties and adhesion of root sealers. The aim of this work was to evaluate the effect of different moisture on the constitution of bioceramic sealers. Materials and methods The sealers were evaluated before mixing, and after setting using X-ray diffraction (XRD), Energy Dispersive Analysis (EDX) and Scanning Electron Microscope (SEM) techniques. Twenty four extracted teeth were prepared and assigned to four groups according to the moisture conditions: (1) dry: using ethanol as final irrigation, (2) normal: using paper points until the last one appeared dry, (3) moist: using a Luer adapter for 5 s followed by 1 paper point, and (4) wet: the canals remained totally flooded. The roots were filled with MTA Fillapex® and Endosequence® BC and kept in phosphate buffer solution at 37 °C for 10 days. Each root was sectioned transversally and longitudinally. The sealers harvested from longitudinal sections were analysed using XRD. Whilst the transverse sections were analysed using SEM/EDX. Results The XRD analysis showed MTA Fillapex composed of Bismuth trioxide, calcium silicate and tricalcium aluminate. The intensity of peaks in the wet condition was reduced. Endosequence BC contained mainly calcium silicate, calcium silicate hydrate, zirconia and calcium hydroxide. The wet condition showed a small increase in hydrated calcium silicate. The EDX analysis showed changes in the elemental concentrations with different moisture conditions. The surface morphology differed with different moisture conditions. Conclusion Tested sealers have different constitution that not affected by the degree of moisture. However, it changed their relative quantity.